Structure and topological transport in Pb-doping topological crystalline insulator SnTe (001) film. (1st May 2020) - Yan, C.H.; Wei, F.; Bai, Y.; Wang, F.; Zhang, A.Q.; Ma, S.; Liu, W.; Zhang, Z.D.
Abstract: Topological crystalline insulator (TCI) as a new type of topological materials has attracted extensive research interests for its tunable topological properties. Due its symmetry topological protection essence, the structure investigation provides a solid basement for tuning its topological transport properties. On SrTiO3 (111) substrate, the SnTe film was found to be epitaxial growth only along [001] while not [111] direction. The detailed structural study was performed and a structural model was proposed to elucidate epitaxial growth of the SnTe (001) film. The transport properties of SnTe (001) film were further investigated and a typical weak anti-localization effect was observed. By Pb-doping into SnTe, the bulk carriers were inhibited and its topological surface states were strengthened to induce the enhanced surface transport contribution. With tunable multiple transport channels from the even Dirac cones, the TCI SnTe film systems will have the potential application in future spintronics devices.